Enhancing secondary-school mathematics teachers’ ability to notice argumentation through an argumentation classroom situations-based course - Samaher Nama; Michal Ayalon (Humanities & Social Sciences Communications)
Abstract This study explores changes in secondary-school mathematics teachers’ noticing of argumentation during a university course designed for this purpose. Thirty-one teachers analyzed written argumentation classroom situations (ACSs) at four points, focusing on two sub-skills: attending to structural and dialogic aspects of argumentation and interpreting the argumentation through various lenses (task characteristics, teaching strategies, cognitive and affective student characteristics, and socio-cultural characteristics). Analysis of the teachers’ ACS reports revealed changes in teachers’ noticing of various dimensions associated with argumentation. Analysis of teachers’ written reflections and semi-structured interviews provided insights into the experience that supported the change in their noticing of argumentation. The study provides evidence of the potential of the course activities for teachers’ learning to notice key aspects of argumentation.